Analysis of the Level of Dysphagia, Anxiety, and Nutritional Status Before and After Speech Therapy in Patients with Stroke - Drozdz, Daniela; Mancopes, Renata; Silva, Ana Maria Toniolo; Reppold, Caroline (International Archives of Otorhinolaryngology, 2014)
Introduction: The rehabilitation in oropharyngeal dysphagia evidence-based implies the relationship between the interventions and their results.Objective: Analyze level of dysphagia, oral ingestion, anxiety levels and nutritional status of patients with stroke diagnosis, before and after speech therapy.Method: Clinical assessment of dysphagia partially using the Protocol of Risk Assessment for Dysphagia (PARD), applying the scale Functional Oral Intake Scale for Dysphagia in Stroke Patients (FOIS), Beck Anxiety Inventory (BAI) and the Mini Nutritional Assessment MNA®. The sample consisted of 12 patients, mean age of 64.6 years, with a medical diagnosis of hemorrhagic and ischemic stroke and without cognitive disorders. All tests were applied before and after speech therapy (15 sessions). Statistical analysis was performed using the chi-square test or Fisher's exact test, McNemar's test, Bowker's symmetry test and Wilcoxon's test.Results: During the pre-speech therapy assessments, 33.3% of patients had mild to moderate dysphagia, 88.2% did not receive food orally, 47.1% of the patients showed malnutrition and 35.3% of patients had mild anxiety level. After the therapy sessions, it was found that 33.3% of patients had mild dysphagia, 16.7% were malnourished and 50% of patients had minimal level of anxiety.Conclusion:  There were statistically significant evolution of the level of dysphagia (p = 0.017) and oral intake (p = 0.003) post-speech therapy. Although not statistically significant, there was considerable progress in relation to the level of anxiety and nutritional status.
Keywords: swallowing disorders; anxiety; nutritional status; rehabilitation